Light-Induced Indeterminacy Alters Shade-Avoiding Tomato Leaf Morphology . Issue 3 (17th September 2015) - Chitwood, Daniel H.; Kumar, Ravi; Ranjan, Aashish; Pelletier, Julie M.; Townsley, Brad T.; Ichihashi, Yasunori; Martinez, Ciera C.; Zumstein, Kristina; Harada, John J.; Maloof, Julin N.; Sinha, Neelima R.
Abstract : Shade avoidance increases indeterminacy in the initiating leaf primordium, increasing leaf complexity and serration through a heteroblasty-independent mechanism. Abstract: Plants sense the foliar shade of competitors and alter their developmental programs through the shade-avoidance response. Internode and petiole elongation, and changes in overall leaf area and leaf mass per area, are the stereotypical architectural responses to foliar shade in the shoot. However, changes in leaf shape and complexity in response to shade remain incompletely, and qualitatively, described. Using a meta-analysis of more than 18, 000 previously published leaflet outlines, we demonstrate that shade avoidance alters leaf shape in domesticated tomato ( Solanum lycopersicum ) and wild relatives. The effects of shade avoidance on leaf shape are subtle with respect to individual traits but are combinatorially strong. We then seek to describe the developmental origins of shade-induced changes in leaf shape by swapping plants between light treatments. Leaf size is light responsive late into development, but patterning events, such as stomatal index, are irrevocably specified earlier. Observing that shade induces increases in shoot apical meristem size, we then describe gene expression changes in early leaf primordia and the meristem using laser microdissection. We find that in leaf primordia, shade avoidance is not mediated through canonical pathways described in mature organs but rather through the expression of KNOTTED1-LIKE HOMEOBOX and other indeterminacy genes, altering known developmental pathways responsible for patterning leaf shape. We also demonstrate that shade-induced changes in leaf primordium gene expression largely do not overlap with those found in successively initiated leaf primordia, providing evidence against classic hypotheses that shaded leaf morphology results from the prolonged production of juvenile leaf types.